Sosialisasi Pembelajaran Berdiferensiasi dalam Program Merdeka Belajar di SMP Gajah Mada Medan - Beslina Afriani Siagian; Sri Natalia Situmorang; Roida Siburian; Angelin Sihombing; Ruth Yuni Ria Harefa; Suci Ramadhani; Alexandra Sitorus (Indonesia Berdaya, 2022)
The purpose of this service is to help each student grow as much as possible according to his abilities and help each teacher know the progress of each student and the development of the class as a whole. One of the social problems faced during the COVID-19 pandemic is the decline in students' motivation and interest in participating in learning. The online system using the application is not enough to help students increase student motivation. This PkM activity will be held on February 2-26, 2022, at: 13.30 - 15.30 WIB which is located at the Gajah Private Junior High School Medan. The number of students as the PkM implementation team is 6 people, the priority is for Class VII, VIII-A, VIII-B SMP students. The first time the implementation was carried out for 2 hours and for 3 meetings by conducting briefing and teaching to students in grades VII, VIII-A, VIII-B of SMP Swasta Gajah Medan. The impact obtained from this PkM are various types of positive activities that can be carried out in encouraging student interest in learning and also activities that foster students' communication ethics, as well as generate creativity in developing the potential of each student in a social and social environment